International Monetary Fund Annual Report 1948. (Annual Report of the Executive Board; Annual Report of the Executive Board ;, 1948)
This paper reviews key findings of the IMF's Annual Report for the fiscal year ended April 1948. The report highlights that during 1947 and in the early part of 1948, considerable progress was made in strengthening the economies that suffered devastation and dislocation as a result of the war. Over the world, generally production rose and recovery continued, despite widespread political tension and conflict, and disturbances. In nearly all countries, however, the need and demand for goods continued to be abnormally great, and there were increasing difficulties in meeting international payments for import surpluses.